2005
DOI: 10.1007/s10582-005-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Brittle-ductile behavior in 3D iron crystals

Abstract: We present large scale molecular dynamic (MD) simulations in bcc iron containing a relatively long Griffith crack loaded in mode I at a temperature of 0 K and 300 K. We use N-body potentials of Finnis-Sinclair type. The paper also includes a stress analysis performed in the framework of anisotropic fracture mechanics and on the atomic level as well. It enables us to understand why at 0 K brittle fracture in MD is detected, while at 300 K ductile behavior at the crack front in MD is monitored, starting from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…He revealed that this change can be completed within a 10 K temperature interval due to the generation of a crack-tip ledge for dislocation emission. Moreover, other brittle to ductile transitions were also observed in simulations [18,19] of single crystal Fe. As mentioned above, previous atomic level simulations have mainly focused on the study of fracture in metals like Al, Ni, Si, and Fe, however very little work has been done on the initial formation of cracks in copper polycrystals, so it is of great interest to investigate the fracture properties of Cu poly-crystal.…”
Section: Introductionmentioning
confidence: 61%
“…He revealed that this change can be completed within a 10 K temperature interval due to the generation of a crack-tip ledge for dislocation emission. Moreover, other brittle to ductile transitions were also observed in simulations [18,19] of single crystal Fe. As mentioned above, previous atomic level simulations have mainly focused on the study of fracture in metals like Al, Ni, Si, and Fe, however very little work has been done on the initial formation of cracks in copper polycrystals, so it is of great interest to investigate the fracture properties of Cu poly-crystal.…”
Section: Introductionmentioning
confidence: 61%
“…The nominal shear (slip) stress τ from the applied stress σ A (Schmid factors) for the slip systems is given by the following relations in our case: These values follow from the results of block like shear simulations in perfect bcc iron crystals, presented in [18,19,20]. Further details are given below.…”
Section: Results Up To Fracture In Dependence On Sample Sizementioning
confidence: 88%
“…Figure 13 shows that up to the time of the surface dislocation emission, where the peak in figure 13(a) occurs, the emission process is driven mainly by the interplanar stress component coming from the potential energy. The peak value in figure 13(a) slightly precedes the time t e = 6869 h in table 2 and its magnitude corresponds to τ MD = 15.1 GPa , which overcomes the stress barrier τ disl = 14.5 GPa in equation (3) for the slip system 〈111〉 {011} following from BLS simulations in [19] for this slip system in a perfect bcc iron crystal with the potential in use. This implies that the dislocation emission in MD is realized in accordance with the Rice model [7b] for 0 K. The level of τ bV (011) in figure 13(b) coming from the kinetic energy before the time t e is very low.…”
Section: Results Up To Fracture In Dependence On Sample Sizementioning
confidence: 89%
“…Crack (001)[010] (crack plane/crack front) under monotonic uniaxial tension can produce dislocations in 3D bcc iron crystals [1] in the available inclined slip systems <111>{101}, while the crack (-110)[110] can emit dislocations in the inclined slip systems <111>{112}, both under monotonic tension [2][3] or cyclic loading [4] in mode I. It occurs at low temperature [2] but also at room temperature [3,4] as experiments on iron crystals [4][5] confirmed.…”
Section: Introductionmentioning
confidence: 99%